Quasi-static compressive performance of 3D printed polymer composite cellular cubic structures-an experimental study - Amran, Abdul Hadi; Nurulain Nadhirah, Shaipizaman; Mohd Amir Shahlan, Mohd Aspar; Mohd Rashidi, Salim; Hadi, Manap (Institute of Advanced Engineering and Science (IAES), 2024)
Ammonia gas is a colorless gas that is known for its pungent odor. It is commonly used in various industries, such as agriculture, refrigeration, and chemical manufacturing. This paper provides a comprehensive overview of various technologies employed in ammonia gas sensors. The objective is to compare and identify the optimum method to detect ammonia gas. The review encompasses catalytic gas sensors, metal oxide gas sensors, polymer conductivity gas sensors, optical gas sensors, and indirect gas sensors, detailing their respective operational principles. Additionally, the advantages and disadvantages of each technology for ammonia gas detection are outlined. All these technologies have been used for many applications and some of them have been commercialized. Some sensor characteristics suggestions are also stated in order to develop an improved optical ammonia sensor for industrial applications.